Evolving voluntary rules for the operation of the European Central Bank - David G. Mayes (Bank of Finland, 1998)
This paper argues that, despite the substantial independence offered by the Maastricht Treaty, the ESCB will wish to bind itself by a set of voluntary rules in the conduct of monetary policy.This binding will occur because of the demands of policy itself.The ESCB as such has no history of a successful pursuit of price stability, although it can borrow some reputation in this from the existing national central banks.The ESCB will therefore need to make a H5 and verifiable precommitment about how it will run monetary policy if it is to be seen as highly credible by all those who can affect prices.The paper surveys the types of rules and rule systems adopted by other central banks and draws conclusions for the ESCB, which require it to be open, straightforward and highly transparent in its conduct of policy.This openness will not only help to dispel any fears that the ESCB will be subject to covert influence to follow objectives other than price stability but it will at the same time help fill the "democratic deficit" attached to such an independent institution.It will need to persuade the public at large and governments, the European Parliament and financial markets in particular that it is pursuing price stability effectively and at minimum cost.Thus, although external sanctions may appear limited, the ESCB is likely to choose to make itself highly "accountable" in the conduct of policy and hence dispel much of the deficit.The paper concludes that action is required now to commit the ESCB to this approach.
URN:NBN:fi:bof-20140807281
Keywords: 330; European Central Bank; monetary policy; transparency; accountability; voluntary rules